Sediment accumulation in an 8 inch sewer pipe for a sample of various particles obtained from the streets of Karbala city, Iraq - Kokaz Mohammed Aswad; Nile Basim K.; Hassan Waqed H. (Open Engineering)
This work investigates the intricate interplay between particle size and water flow velocity in connection to sedimentation within the sewage systems. The experimental design involves simulating the sedimentation process in a laboratory setup using an 8 inch unplasticized polyvinyl chloride pipe with a controlled slope. Three factors of flow and discharge velocity detailed in this work are particle size, velocity, and sedimentation rate, which are determined through calculations based on the Manning equation. For the numerical simulations, the software packages Fluent and Rocky were used. Sediment transportation under laminar flow conditions can be analyzed by means of numerical simulation. The size, shape, and velocity of the fluid in which the particles are suspended are only a few of the variables taken into consideration while assessing the drag force acting on the particles. The results show that the smaller particles escape the entry further because they are more movable within the conduit. Conversely, it is demonstrated that increased settling pressures near the entrance increase the probability of larger particle sizes settling. Higher water velocities have been found to have a favorable effect on the sediment mobility, which decreases the particle accumulation. This study presents practical methods to mitigate sedimentation in sewage systems, including increasing water flow rates and employing filtration methods to keep larger particles out of the system. This work adds a great deal to the body of information previously known on sedimentation behavior in these systems with its incisive finds that may boost the longevity and efficiency of sewage systems. More research is required to determine the value of the proposed treatments.